2022
DOI: 10.1002/ps.6865
|View full text |Cite
|
Sign up to set email alerts
|

Helicoverpa armigera herbivory negatively impacts Aphis gossypii populations via inducible metabolic changes

Abstract: BACKGROUND: Helicoverpa armigera and Aphis gossypii are two important insect species that feed on cotton plants. These insects have distinct abilities to induce plant resistance and tolerate plant toxins, which results in interspecific competition imbalance that may be fatal to the low-tolerance A. gossypii and force these insects to develop avoidance behaviors and subsequently separate from their niche. We implemented ecological experiments to test the effects of H. armigera-induced plant resistance and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…ROS accumulation can induce plants to exhibit stimulated antioxidant enzyme activity activities such as phenylalanine ammonia lyase (PAL) and glutathione reductase, leading to an increase in the production of secondary metabolites such as flavonoids and tannins (Gautam et al 2023 ; Ho et al 2020 ; Han and Yuan 2004 ). These secondary metabolites have negative impacts on insect populations, such as inhibiting insect development, increasing mortality, reducing feeding efficiency, and decreasing protein utilization efficiency (Gautam et al 2023 ; Mierziak et al 2014 ; Zheng et al 2022 ). Cheah et al ( 2020 ) found that the accumulation of PAL potentially enhances the resistance of a C. medinalis -resistant rice variety (Qingliu) by priming the biosynthesis of essential flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…ROS accumulation can induce plants to exhibit stimulated antioxidant enzyme activity activities such as phenylalanine ammonia lyase (PAL) and glutathione reductase, leading to an increase in the production of secondary metabolites such as flavonoids and tannins (Gautam et al 2023 ; Ho et al 2020 ; Han and Yuan 2004 ). These secondary metabolites have negative impacts on insect populations, such as inhibiting insect development, increasing mortality, reducing feeding efficiency, and decreasing protein utilization efficiency (Gautam et al 2023 ; Mierziak et al 2014 ; Zheng et al 2022 ). Cheah et al ( 2020 ) found that the accumulation of PAL potentially enhances the resistance of a C. medinalis -resistant rice variety (Qingliu) by priming the biosynthesis of essential flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Potted cotton plants (G. hirsutum CCRI 49) were transplanted into soil pots (15 × 17 cm), then put it into environmentally controlled chambers (50 × 60 × 110 cm) and maintained under either a 14 h (long day) or 10 h (short day) light period at 25 ± 2 • C and 65-70% relative humidity till the plants reached the four-leaf stage for further testing [13]. Subsequently, each cotton plant was placed in a 30 cm squared cage, and nine adult A. suturalis (starved for 12 h before inoculation) were introduced onto the leaves.…”
Section: Plant Materials and Insect Infestationmentioning
confidence: 99%
“…Increasing evidence suggests that the JA signaling pathway is crucial in plant defense, contributing to rice resistance against the leaf folder (Cnaphalocrocis medinalis) [12]. JA also mediates cotton plant resistance induced by Helicoverpa armigera and affects the growth and development of Aphis gossypii [13]. When rice plants are attacked by the brown plant hopper (Nilaparvata lugens), JA activates rice defense responses and gibberellin catabolism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Helicoverpa armigera (Lepidoptera: Noctuidae) is a worldwide pest known to infest over 200 host plants, including cotton, tomato, pepper, potato, and various other crops and wild plants ( Zheng et al, 2022 ). It occurs frequently in large crop-growing countries such as China, India, and Australia.…”
Section: Introductionmentioning
confidence: 99%